Amentoflavone inhibits tumorsphere formation by regulating the Hedgehog/Gli1 signaling pathway in SUM159 breast cancer stem cells. (October 2019) - Bao, Cheng; Chen, Jing; Kim, Jin Tae; Qiu, Shuai; Cho, Jae Seok; Lee, Hong Jin
Graphical abstract: Highlights: Amentoflavone inhibited tumorsphere formation of basal-like breast cancer stem cells (CSCs). Amentoflaovne regulated the expression of CSC markers, CD44, CD24, ALDH1, OCT4 and NANOG in SUM159 breast CSCs. Amentoflavone suppressed Hedgehog signaling mediators, Gli1 and Smo, leading to inhibition of breast CSCs stemness. Abstract: A novel anticancer approach is to target cancer stem cells (CSCs), a rare subpopulation potentially associated with metastasis, resistance to chemotherapy, and recurrence of cancers. This study aimed to investigate the effects of amentoflavone, a natural compound identified from Chamaecyparis obtusa, on stemness of basal-like SUM159 breast CSCs, and its underlying mechanism of action. We found that amentoflavone suppressed tumorsphere formation and regulated the expression of the stem cell markers CD44, CD24, and ALDH1 in a dose dependent manner, and inhibited Hedgehog (Hh) signaling by down-regulating Smo, Gli1, OCT4, and NANOG. Knock-down of Gli1 by siRNA significantly affected the expression of CD44, CD24, ALDH1, OCT4, and NANOG, and reduced tumorsphere formation efficiency in SUM159 breast CSCs. Our findings indicate that amentoflavone inhibits SUM159 breast cancer stemness by suppressing Hh/Gli1 signaling, and is a potent agent for targeting breast CSCs.